STUDI META-ANALISIS HUBUNGAN ANTARA GAYA KEPEMIMPINAN DAN KEPUASAN KERJA - Mauliana Fitosyah; Budi Sutiono Pratama Nugraha (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This meta-analysis aims to investigate the relationship between leadership style and job satisfaction by synthesizing data from 20 empirical studies conducted in Indonesia. The studies cover various populations such as civil servants, educators, and private sector employees. The analysis was conducted using a random-effects model via Jamovi software to address inter-study heterogeneity. The results showed a significant and positive effect size (r = 0.79, 95% CI [0.65, 0.94], p < 0.001), indicating a strong relationship between leadership style and job satisfaction. High heterogeneity (I² = 89.6%) indicates substantial variation across studies. Assessment of publication bias using Fail-Safe N, Begg and Mazumdar correlation, and Egger regression showed no indication of significant bias. Visualization via forest plots demonstrated consistent positive contributions from most studies toward the overall effect. These results emphasize the importance of applying transformational and participatory leadership styles in enhancing job satisfaction and organizational effectiveness. This study recommends that organizations strengthen leadership practices that promote participation, motivation, and harmonious work relationships.